PEMBAHASAN SEPUTAR MUHADDIS, TADWIN HADIS, DAN KUTUB AS-SITTAH - Dany Indra Permana; Dzulkifli Hadi Imawan (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2022)
This study attempts to explain several major topics in hadith and hadith science, namely about who Muhaddis are, how the dynamics of tadwin hadiths are, and about the kutubussittah. Research on tadwin hadith or bookkeeping and codification of hadith is very interesting because with it, can be seen how the efforts of scholars in maintaining the hadith of the Prophet and showing the greatness of the methods and systematics of authenticating the hadith used. This research was conducted using the literature study method, with book references from mutaqoddimin scholars and contemporary scholars. The results of this study show how the criteria of a Muhaddis and how the dynamics of hadith tadwin until the books of hadith scholars can be studied to this day. Abstrak Kajian ini berusaha menerangkan beberapa topik besar dalam Hadis dan ilmu Hadis, yaitu tentang siapa itu Muhaddis, bagaimana dinamika tadwin Hadis, dan tentang kutub as-sittah. Penelitian tentang tadwin Hadis atau pembukuan dan kodifikasi Hadis sangatlah menarik karena dengannya dapat diketahui bagaimana jerit payah ulama dalam menjaga Hadis Nabi serta menunjukkan kehebatan metode dan sistematika penshahihan Hadis yang dipakai. Penelitian ini dilakukan dengan metode studi pustaka, dengan referensi buku dari ulama mutaqoddimin maupun ulama zaman ini. Hasil penelitian ini menunjukkan bagaimana kriteria seorang Muhaddis serta bagaimana dinamina tadwin Hadis sampai kitab para ulama Hadis bisa dipelajari sampai hari ini.